A finding at the Natural History Museum of Florence affords the holotype designation of Orchestia stephenseni Cecchini, 1928 (Crustacea: Amphipoda: Talitridae) - Brutto, Sabrina Lo (Zootaxa, 2017)
The beach flea Orchestia stephenseni has been originally described by Cecchini twice (1928, 1929) from the La Spezia type locality (northern Tyrrhenian Sea, Italy), and successively re-described by Karaman (1973) and Iaciofano & Lo Brutto (2016).